The Social and Community-Creative Value of the Churchyard Areas of Rural Parish Churches of the Archdiocese of Lublin - Kulesza, Piotr; Żak-Kulesza, Małgorzata (Roczniki Kulturoznawcze, 2024)
Currently, there is a growing need for spaces to meet social needs. One of such spaces is the parish, which is not only the basic organizational unit with a pastoral function, but should also be a “community of communities” and implement the idea of socialized pastoral care. This involves not just catechesis but also building social bonds, integrating local communities, and creating place identity, which is crucial amid increasing secularization. Therefore, it is worth asking whether contemporary parishes are predisposed to fulfill social and community functions, especially in the spatial dimension? This article assesses whether contemporary parishes are equipped to fulfill social and community functions, particularly in the spatial dimension. The evaluation focused on five categories: spatial, vegetation, utility-infrastructure, communication, and settlement, using point valuation and SWOT analysis. The research found that only five out of 183 rural parish churches have the capability to meet these needs in three different categories. No church grounds received the highest number of points in four or all five categories.